CHARACTERIZATION AND ANATOMIC DIFFERENCES OF WOODS OF Retrophyllum rospigliosii AND Prumnopitys harmsiana FROM THE PROVINCE OF SAN IGNACIO, PERU - BASELLY-VILLANUEVA, Juan Rodrigo (2022)
The species Retrophyllum rospigliosii (Pilg.) C. N. Page (Female Romerillo) and Prumnopitys harmsiana (Pilg.) de Laub. (Male Romerillo) are conifers native to Peru and form an important part of the cloud forests of the Department of Cajamarca. Their woods are in demand in the local market for carpentry works, due to their physical-mechanical properties and good finish; however, information on the microscopic structure is scarce. The aim of this work was to characterize and determine the anatomical differences in the wood of the two species and thus expand the knowledge of their structures. Samples were obtained by non-destructive method, prepared and studied by microtomy and maceration; whose description was made using the IAWA standard. The main qualitative characteristic that allows differentiating them is the presence of diffuse parenchyma in Retrophyllum rospigliosii and absent in Prumnopitys harmsiana.